2023
DOI: 10.3390/w15040803
|View full text |Cite
|
Sign up to set email alerts
|

Voices in Shaping Water Governance: Exploring Discourses in the Central Rift Valley, Ethiopia

Abstract: As is the case elsewhere in the world, water governance in Ethiopia is a by-product of a complex set of various global and local socio-political, economic, and ecological discourses and narratives. However, the many competitive and often conflicting discourses on shaping water governance in the Ethiopian Central Rift Valley (CRV) have not been examined and chronicled. This paper investigates the different discourses, narratives, and debates of water governance and their implications for satisfying the growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 58 publications
0
14
0
1
Order By: Relevance
“…In particular, the two neighboring lakes, Abijata and Shalla, in CRV are of special importance to wildlife by providing feeding and breeding grounds for a rich bird fauna of over 360 species, including both resident and migratory birds. The two lakes have been enclosed as part of a national park since the 1970s [26,34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the two neighboring lakes, Abijata and Shalla, in CRV are of special importance to wildlife by providing feeding and breeding grounds for a rich bird fauna of over 360 species, including both resident and migratory birds. The two lakes have been enclosed as part of a national park since the 1970s [26,34].…”
Section: Methodsmentioning
confidence: 99%
“…(meters above sea level) to more than 4200 m.a.s.l. [25,26]. The CRV is a center of biodiversity, acting as a migration corridor for critical bird species [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Pendekatan universal diajukan yang mengatasi baik ketidaksetaraan maupun keberlanjutan (menjaga keadilan antar-generasi), dan menghormati hak asasi manusia terhadap layanan air dan sanitasi. Tindakan tata kelola yang sesuai, seperti regulasi dan penegakan standar yang disepakati, menjadi esensial untuk memastikan kualitas keseluruhan tubuh air dari waktu ke waktu (Bantider et al, 2023). Pengendalian polusi akan meningkatkan kualitas air di sungai dan danau serta mendukung fungsi ekosistem dengan mengurangi zat-zat organik dan mineral yang dapat merusak pasokan oksigen (UN-Water, 2014).…”
Section: Hasil Dan Pembahasan Hasil Penelitianunclassified
“…Fast growing construction, weak formal institution, weak environmental protection law, socio-economic, cultural, legal and environmental and institutional problems are constraints for community based development in Ethiopia (Tesfaye, 2017a;Bantider et al, 2023). Teressa (2015) study revealed that there is lack of social network, norms and social trust in the Wenchi community based ecotourism.…”
Section: Other Challengesmentioning
confidence: 99%